Functional Implications of Active N6-Methyladenosine in Plants - Zheng, Hongxiang; Li, Simin; Zhang, Xiansheng; Sui, Na (Frontiers in Cell and Developmental Biology, 2020)
N6-methyladenosine (m6A) is the most common type of eukaryotic mRNA modification and has been found in many organisms, including mammals and plants. It has important regulatory effects on RNA splicing, export, stability, and translation. The abundance of m6A on RNA depends on the dynamic regulation between methyltransferase (“writer”) and demethylase (“eraser”), and m6A binding protein (“reader”) exerts more specific regulatory function by binding m6A modification sites on RNA. Progress in research has revealed important functions of m6A modification in plants. In this review, we systematically summarize the latest advances in research on the composition and mechanism of action of the m6A system in plants. We emphasize the function of m6A modification on RNA fate, plant development and stress resistance. Finally, we discuss the outstanding questions and opportunities exist for future research on m6A modification in plant.